Hypothyroidism. Issue 10101 (23rd September 2017) - Chaker, Layal; Bianco, Antonio C; Jonklaas, Jacqueline; Peeters, Robin P
Summary: Hypothyroidism is a common condition of thyroid hormone deficiency, which is readily diagnosed and managed but potentially fatal in severe cases if untreated. The definition of hypothyroidism is based on statistical reference ranges of the relevant biochemical parameters and is increasingly a matter of debate. Clinical manifestations of hypothyroidism range from life threatening to no signs or symptoms. The most common symptoms in adults are fatigue, lethargy, cold intolerance, weight gain, constipation, change in voice, and dry skin, but clinical presentation can differ with age and sex, among other factors. The standard treatment is thyroid hormone replacement therapy with levothyroxine. However, a substantial proportion of patients who reach biochemical treatment targets have persistent complaints. In this Seminar, we discuss the epidemiology, causes, and symptoms of hypothyroidism; summarise evidence on diagnosis, long-term risk, treatment, and management; and highlight future directions for research.